What is the potential of linguistic landscape as a provision for language learning? Examples from language education contexts - Romanowski, Piotr (Neofilolog, 2026)
This article explores the potential of linguistic landscape (LL) as a valuable resource for language learning, emphasizing its multifaceted role in fostering language acquisition, language awareness and intercultural competence. LL serves as an authentic, multimodal and socio-culturally embedded source of linguistic input that can enrich traditional pedagogical approaches. The paper highlights how English’s pervasive presence in LL reflects global sociolinguistic trends, while also examining how minority and heritage languages are represented, often influenced by political and community practices, thus offering opportunities for language revitalization and identity affirmation. Further, engaging with LL promotes pragmatic competence by exposing learners to real-life language use, indirect speech acts and cultural metaphors, while its multimodal and translanguaging features support multiliteracies and intercultural understanding. The concept of the schoolscape extends these ideas to educational environments, where spatial and linguistic arrangements can reinforce or challenge language ideologies, impacting identity and power dynamics. Pedagogical applications, including classroom projects, virtual explorations and research initiatives, demonstrate LL’s capacity to connect formal learning with everyday language environments. Overall, the article underscores LL’s potential to make language learning more contextualized, socially relevant, and empowering, advocating for its systematic integration into diverse educational frameworks to maximize its benefits across sociolinguistic contexts.